Novel Pentablock Copolymers as Thermosensitive Self-Assembling Micelles for Ocular Drug Delivery - Mitra Alami-Milani; Parvin Zakeri-Milani; Hadi Valizadeh; Roya Salehi; Sara Salatin; Ali Naderinia; Mitra Jelvehgari (Advanced Pharmaceutical Bulletin, 2017)
Many studies have focused on how drugs are formulated in the sol state at room temperature leading to the formation of in situ gel at eye temperature to provide a controlled drug release. Stimuli-responsive block copolymer hydrogels possess several advantages including uncomplicated drug formulation and ease of application, no organic solvent, protective environment for drugs, site-specificity, prolonged and localized drug delivery, lower systemic toxicity, and capability to deliver both hydrophobic and hydrophilic drugs. Self-assembling block copolymers (such as diblock, triblock, and pentablock copolymers) with large solubility variation between hydrophilic and hydrophobic segments are capable of making temperature-dependent micellar assembles, and with further increase in the temperature, of jellifying due to micellar aggregation. In general, molecular weight, hydrophobicity, and block arrangement have a significant effect on polymer crystallinity, micelle size, and in vitro drug release profile. The limitations of creature triblock copolymers as initial burst release can be largely avoided using micelles made of pentablock copolymers. Moreover, formulations based on pentablock copolymers can sustain drug release for a longer time. The present study aims to provide a concise overview of the initial and recent progresses in the design of hydrogel-based ocular drug delivery systems.